No Parkin Zone: Mitophagy without Parkin. Issue 11 (November 2018) - Villa, Elodie; Marchetti, Sandrine; Ricci, Jean-Ehrland
Abstract : Mitochondria are essential highly dynamic organelles that provide the necessary energy for a variety of different processes, such as survival, proliferation, and migration. In order to maintain an intact mitochondrial network, cells have developed quality control systems that allow the removal of damaged or superfluous mitochondria by selective mitochondrial autophagy called mitophagy. Although the parkin/PINK1 axis is often considered the main regulator of mitophagy, a growing body of evidence has shown that this pathway is not unique and that mitophagy can still be functional in the absence of parkin. Here, we will review recent literature describing parkin-independent mitophagy and its role in various physiopathological conditions, therefore representing potential new targets to treat diseases affected by dysregulated mitophagy. Highlights: Mitophagy can be defined as the selective elimination of damaged mitochondria or mitochondria in excess. Mitophagy is a form of evolutionarily conserved macroautophagy, from yeast to fly and human. Mitophagy is acting as a control quality surveillance system allowing the maintenance of the mitochondrial network integrity and promoting cellular homeostasis and survival. Parkin/PINK1 mitophagy pathway is not responsible for all the mitophagy processes. Several pathways have been identified as regulators of parkin-independent mitophagy in physiological and pathological conditions.